2021
DOI: 10.1039/d1cc01187a
|View full text |Cite|
|
Sign up to set email alerts
|

Assembly of fluorinated chromanones via enantioselective tandem reaction

Abstract: The enantioselective synthesis of fluorinated tricyclic chromanones with multiple vicinal stereogenic centers has been realized for the first time, through the tandem reaction between 2-fluorinated 1-(2-hydroxyaryl)-1,3-diketones and α,β-unsaturated aldehydes. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Subsequently, we further expanded the scope of this work by applying fluorine‐containing substrates 61 [51] . Moreover, replacing the final oxidation of the tandem process with acylation reaction could also avoid epimerization in this work.…”
Section: Benzopyran‐fused Polycyclic Acetalsmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, we further expanded the scope of this work by applying fluorine‐containing substrates 61 [51] . Moreover, replacing the final oxidation of the tandem process with acylation reaction could also avoid epimerization in this work.…”
Section: Benzopyran‐fused Polycyclic Acetalsmentioning
confidence: 97%
“…Subsequently, we further expanded the scope of this work by applying fluorine-containing substrates 61. [51] Moreover, replacing the final oxidation of the tandem process with acylation reaction could also avoid epimerization in this work. The same configuration of products indicated that very similar transition state has been involved in all cases (Scheme 31).…”
Section: Benzopyran-fused Polycyclic Acetalsmentioning
confidence: 99%
“…In the past few years, we have been interested in the stereoselective construction of valuable heterocycles with multi-stereocenters via organocatalyzed domino reactions. [14] As part of our ongoing efforts, we conducted an organocatalyzed stereoselective domino reaction of isatylidene malononitriles and alkenesubstituted 1,3-diketones to provide a facile approach to construction of complex tetrahydroxanthone framework with three contiguous stereocenters. [14d] Considering the potential applications of this skeleton, developing new catalytic systems to realize the diversityoriented construction of chiral tetrahydroxanthone scaffold is still meaningful.…”
mentioning
confidence: 99%
“…However, aryl- or alkenyl-substituted acyclic diketones have not been successfully reported for this [3 + 3] cycloaddition . As part of our continuous interest in the construction of O , O -acetal-fused tricyclic skeletons using 1-(2-hydroxyaryl)-1,3-butanediones through organocatalyzed domino reaction, we attempted to construct the spiropyran–oxindole skeleton bearing an O , O -acetal-fused tricyclic motif through the domino reaction between 1-(2-hydroxyaryl)-1,3-butanediones and isatylidene malononitriles (Scheme b).…”
mentioning
confidence: 99%